Evolução do mercado ressegurador mundial - Marin, Evandro Rinolfi (2019)
The objective of this essay is to deal in a historical way with the evolution of the global reinsurance market structure, observing the international development of the market and the resulting dominance of participation of some of the largest reinsurance groups. The essence of this work is the observation about the change that occurred over the years in the market share of these groups which carry out the spraying of risks internationalized. Initially, an exploratory, qualitative and historical introduction about the changes occurred in several reinsurance markets was carried out. However, the focus of this work is the descriptive and quantitative analysis of structured data, exposed from Chapter 2, performed with the application of competitive indicators, such as the Herfindahl-Hirschmann index, Theil's T index and Concentration Ratios, for the confirmation of the hypothesis that the international reinsurance market is not heading to the concentration of market share among a few players or global reinsurance groups, at least, within the historical series analyzed, but rather to current relative maintenance of the concentration level of reinsurance premiums earned by such groups